Keputusan investasi: Peran efek disposisi, perilaku herding, dan persepsi risiko - Nada, Alya Qotrun; Fikri, Muhammad Ali (Journal of Management and Digital Business, 2025)
Investment decisions are a critical part of financial management for both individuals and institutions and are often influenced by psychological and behavioral factors. This study analyzes the effects of the disposition effect, herding behavior, and risk perception on investment decisions among FAC Sekuritas investors. Using a quantitative design, primary data were collected through a questionnaire administered to 123 FAC Sekuritas investors selected via purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that the disposition effect has a positive effect on investment decisions, and herding behavior also has a positive effect on investment decisions. In addition, risk perception is shown to have a positive effect on investment decisions. These findings suggest that behavioral factors and risk perception help shape retail investors’ decisions, highlighting the need for securities firms and regulators to strengthen investor education that emphasizes awareness of behavioral biases and sound risk understanding.